Methods For Implementing The Methodology Of Teaching Biology On The Basis Of A Functional Approach (Eurasian Journal of Learning and Academic Teaching, 2024)
The formation of functional literacy in the lesson is a condition for the development of the competence of students. Innovative technologies in the teaching of biology are fundamentally new methods of interaction between teachers and schoolchildren, ensuring effective achievement of the result of pedagogical activity. The use of new modules in education makes it possible to develop the functional literacy of the student